2005
DOI: 10.3354/meps294181
|View full text |Cite
|
Sign up to set email alerts
|

Size matters: bleaching dynamics of the coral Oculina patagonica

Abstract: A 2-yr continuous photographic monitoring of a tagged population of the encrusting coral Oculina patagonica in the Mediterranean was conducted to study intra-colonial bleaching dynamics and the relationship between bleaching, mortality, and colony size. Surveys of non-tagged colonies showed that during the peak bleaching season (August, sea surface temperature = 31°C), non-bleached colonies were frequently found to be small colonies averaging 4.6 ± 2.3 cm in diameter. Within tagged colonies, percent bleached s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 49 publications
4
68
2
Order By: Relevance
“…Individual colony bleaching patterns, which typically proceed from the tips or edges towards the base or centre (see e.g. Shenkar et al, 2005), also conform to the known colonyscale topology of MI, wherein the tips and edges consistently contain zooxanthellae with higher MI (Fang and Chen, 1989;Jones and Yellowlees, 1997). Indeed, Wooldridge (2009a) uses the ATP-dependent CO 2 -limitation model (Fig.…”
Section: Bleaching Thresholds Linked To Zooxanthellae MImentioning
confidence: 75%
“…Individual colony bleaching patterns, which typically proceed from the tips or edges towards the base or centre (see e.g. Shenkar et al, 2005), also conform to the known colonyscale topology of MI, wherein the tips and edges consistently contain zooxanthellae with higher MI (Fang and Chen, 1989;Jones and Yellowlees, 1997). Indeed, Wooldridge (2009a) uses the ATP-dependent CO 2 -limitation model (Fig.…”
Section: Bleaching Thresholds Linked To Zooxanthellae MImentioning
confidence: 75%
“…80% of the colonies undergo bleaching (Kushmaro et al 1998, Israely et al 2001, Fine & Loya 2003. When the water temperature drops, most of the colonies regain their symbiotic algae and recover (Shenkar et al 2005). O. patagonica is a gonochoric coral, in which female and male gonads appear in May and July (respectively) and reach maturity by late August.…”
Section: Introductionmentioning
confidence: 99%
“…Baird and Marshall (2002) reported no association between colony size class and bleaching mortality for scleractinian coral of reproductive size at two locations on the Great Barrier Reef. In contrast, Shenkar et al (2005) reported that large Oculina patagonica coral colonies had higher mortality from bleaching than small colonies, which were less likely to bleach for a site in the Mediterranean Sea. Hoeksema (1991) reported a similar result for Fungiidae corals in the Java Sea.…”
Section: Porites Poritesmentioning
confidence: 90%
“…Coral bleaching diVerentially aVects coral species (Marshall and Baird 2000), coral morphology types (Wnger corals having higher mortality than mounding corals) (Loya et al 2001), and colony size-frequency distributions by removing larger sized colonies (Hoeksema 1991;Loya et al 2001;Shenkar et al 2005). Recently, Ritchie (2006) showed the loss of antibodies in Acropora palmata mucus during 2005 summer bleaching in the Florida Keys.…”
Section: Introductionmentioning
confidence: 99%